Structural Model of a Hydrostatic Cryogenic Liquid Storage and Pressurization Tank in the Food Sector - Raymundo, Carlos (2024)
The demand for high-pressure, operational cryogenic fluid storage systems in specialized laboratories has driven the design of an innovative solution due to the scarcity of specialized equipment in the local market. This article details the design and manufacturing of a portable, long-lasting cryogenic fluid storage tank that meets safety and efficiency requirements, while also facilitating individual cryogenic tests. By applying Pascal’s principle, an effective increase in the pressure of the cryogenic fluid was achieved, which is essential for supplying the system at pressure. The tank incorporates specific inputs and outputs, including an additional input for high-pressure air injection, a safety valve, and a pressure measurement port, highlighting its functionality and autonomy in individual operations. The integration of these features has been validated through simulations and empirical tests, demonstrating significant improvements in temperature retention and structural stability. The results obtained not only demonstrate the feasibility of the design for use in laboratories but also suggest an adaptable model for other applications where access to technology is limited. Having a calibrated pressure gauge with a maximum measurement error of 0.015 psi, which is lower than the allowed 0.025 psi, ensures the quality of measurements during its use. This contribution opens new perspectives for optimizing cryogenic tests and can serve as a reference for future research and technological developments in the field.